Cooling tower performance and the ambiguity of the L/G ratio scheme in optimization: A single cell control volume approach - Mohd Amir F.; Yusoff M.Z.; Abu Hassan S.H. (Elsevier Ltd, 2024)
Present optimization schemes and innovative operation strategies of the cooling tower often encounter unexpected results, which may derail the effort for better efficiency. In some instances, the practice may even cause energy and water wastage. In this study, the single-cell approach is performed numerically, translating the full cooling tower fill into the smallest fundamental state of control volume to investigate the performance ambiguity attributed to the L/G ratio scheme. Two types of surface are proposed to investigate the surface effect. The actual fluid rate inside the fill varies by 2050% between the two fill surfaces, which is relatively higher on the multi-faceted single cell. The Merkel number is integrated into the analysis by examining the liquid-gas interface for heat transfer assessment. The lower fluid rate on the circular single cell generates a higher Merkel number than the multi-faceted single cell. Even though the 32% increase in Merkel number is achieved under various liquid loads on the multi-faceted single cell, approximately half of the operating liquid load leads to decreasing Merkel number. Meanwhile, the reaction axis is introduced to characterize the surface fill under the effect of the liquid load. It is symmetrical on the circular single cell, indicating a positive linear effect to increasing liquid load. On the contrary, the reaction axis is asymmetrical on the multi-faceted single cell suggesting a negative linear effect which also leads to excess unproductive fluid rate. 2023 Elsevier Ltd